PERKEMBANGAN EKONOMI SYARIAH DI INDONESIA - Abdillah Halim (Investama : Jurnal Ekonomi dan Bisnis, 2022)
The development of sharia economic law in the future must increasingly refer to protection for the people by using maqashid sharia as a methodology and perspective. To determine economic law that falls within the scope of muamalah fiqh, a comprehensive mastery of ushul fiqh is absolutely necessary, especially to find and determine the legal illat of ongoing economic practices. Failure to determine illat leads to failure to control the source of the problem. The current Islamic economy only talks a lot about distribution and consumption, a kind of distribution of money and capital that is claimed without usury and halal product certification, and does not appear to talk much about production and all aspects related to it, such as land ownership, resources, capital, and by the private sector and conglomerates, including regarding the fulfillment of labor rights, the destruction of nature by production activities, and so on. The determination of illat and maqashid sharia in the economic field is also expected to pay more attention to material conditions in which unequal production relations among community groups have resulted in economic and political colonization, which is very detrimental to society, especially for those who are in a weak position in terms of capital, resources, and political power.